Swiss Ball Media-Based Horse Kick Skills Development Initiatives for Pencak Silat Extracurricular Students at SMPN 251 Jakarta - Mariana, Chika Cintya; Lubis, Johansyah; Juniarto, Mastri; Rihatno, Taufik (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives. This study focuses on the horse kick technique in Pencak Silat, aiming to determine the improvement in horse kick skills through the use of a Swiss ball in the single artistic category. Materials and Methods. This research employed an action research method involving 20 students from the Pencak Silat extracurricular program at SMPN 251 Jakarta. A horse kick test instrument, consisting of 20 validated assessment aspects reviewed by three Pencak Silat experts, was used for evaluation. The study was conducted in one cycle comprising eight meetings. Results. The initial test results of the horse kick technique showed that the students had an average score of 87.55. At the beginning of the study, only 4 students (20%) met the success criteria. However, by the end of the cycle, all 20 students (100%) successfully improved their horse kick technique. Conclusions. The findings indicate that the use of a Swiss ball effectively enhances horse kick skills among students participating in the Pencak Silat extracurricular program at SMPN 251 Jakarta.